Satisfaction with information and unmet information needs in men and women with cancer - Faller, Hermann; Koch, Uwe; Brähler, Elmar; Härter, Martin; Keller, Monika; Schulz, Holger; Wegscheider, Karl; Weis, Joachim; Boehncke, Anna; Hund, Bianca; Reuter, Katrin; Richard, Matthias; et al. (Journal of cancer survivorship, 2016)
Information needs in cancer patients are high but often not fulfilled. This study aimed to examine the level of perceived information, information satisfaction, and unmet needs in a large sample of cancer patients. Further, we explored associations with emotional distress and quality of life accounting for gender.
Published online: 9 May 2015
Gesehen am 13.05.2020